The Transformation of Tauhid Values in Malay Arts and Culture and Their Relevance to the Islamic Identity of Malay Society - Taufik; Haris Riadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the transformation of tawhid values in Malay cultural arts as part of the internalization process of Islamic teachings in Malay society. This research is important because modernization and globalization have increasingly influenced the existence of Malay culture, which has long been closely associated with Islamic religious and spiritual values. The objectives of this study are to analyze the transformation of tawhid values in Malay cultural arts, describe the forms of internalization of tawhid values in Malay cultural expressions, and examine the relevance of Malay cultural arts in maintaining the Islamic identity of Malay society in the modern era. This study employed a qualitative approach using library research methods. Data were collected from scientific journals, books, and other relevant academic literature and analyzed using content analysis techniques. The findings show that tawhid values in Malay culture have transformed through a process of cultural acculturation without eliminating the local identity of Malay society. Tawhid values are reflected in pantun, syair, gurindam, traditional music, carvings, architecture, and Malay customs as media for da’wah and moral education. This study concludes that Malay cultural arts remain relevant as a means of strengthening Islamic identity and developing the religious character of Malay society in the modern era.